The Influence of planned, repeated, and emergency interruptions on the well-being of military families - Mayo-Theus, Suzanne Mynette (Kansas State University, 2011)
The current military family life is punctuated by a series of events that are not present in the lives of most Americans, most notably the stress, fear, and disruption of lives that accompany the periodic absences of one or both adults in the family. These absences fostered by deployments, challenges of readjustments, coupled with combat injuries have tremendous effects on not only the troops and their families, but also the communities that military families live in as well. This investigation examined how military assistance, family connectedness and community networks contribute to the well-being of families affected by anticipated and repeated deployments that cause family interruptions. Despite the myriad of studies on military deployments and the impact on families, there has been little focus on the spouse and children that relates to their resilience during the deployment process. Using an online national all service unit sample from military spouses (n = 185) who have children and have experienced a recent deployment (n = 153) it was possible to isolated the specific components that influenced the well-being of those affected by deployments. The Influence of Interruptions on Family Well-Being Model—which combines ideas from both the ecological systems and boundary ambiguity perspectives—was tested and utilized in this study. It was disclosed that 45% of the variance in well-being could be explained by knowing how families perceive the deployment process, military assistance, community networks, family connectedness, and how these families coped with periodic family interruptions. These data revealed that deployments have a greater impact than originally conceived and that issues addressing deployments must be placed on the national agenda, particularly where family well-being is concerned. The research findings underscore the importance of family to both the deployed personnel and the ones that they leave home. The implications from this investigation are simple and direct—there needs to be a more comprehensive program for children that employ pre-, during- and post-deployment related issues, such as adjustments to absent parents, developing better responses to the authority structure of the remaining parent, and some program focused on the immediate and long-term psychological needs of the children and their families.
Keywords: Military; Deployments; Families; Ambiguity; Separations; Interruptions; Social Research (0344)